Characterization of Cardiac Anoctamin1 Ca2+‐Activated Chloride Channels and Functional Role in Ischemia‐Induced Arrhythmias. Issue 2 (February 2015) - Ye, Zhen; Wu, Ming‐Ming; Wang, Chun‐Yu; Li, Yan‐Chao; Yu, Chang‐Jiang; Gong, Yuan‐Feng; Zhang, Jun; Wang, Qiu‐Shi; Song, Bin‐Lin; Yu, Kuai; Hartzell, H. Criss; Duan, Dayue Darrel; et al.
<x xml:space="preserve">Abstract</x> Anoctamin1 (ANO1) encodes a Ca2+‐activated chloride (Cl−) channel (CaCC) in variety tissues of many species. Whether ANO1 expresses and functions as a CaCC in cardiomyocytes remain unknown. The objective of this study is to characterize the molecular and functional expression of ANO1 in cardiac myocytes and the role of ANO1‐encoded CaCCs in ischemia‐induced arrhythmias in the heart. Quantitative real‐time RT‐PCR, immunofluorescence staining assays, and immunohistochemistry identified the molecular expression, location, and distribution of ANO1 in mouse ventricular myocytes (mVMs). Patch‐clamp recordings combined with pharmacological analyses found that ANO1 was responsible for a Ca2+‐activated Cl− current (ICl.Ca) in cardiomyocytes. Myocardial ischemia led to a significant increase in the current density of ICl.Ca, which was inhibited by a specific ANO1 inhibitor, T16Ainh‐A01, and an antibody targeting at the pore area of ANO1. Moreover, cardiomyocytes isolated from mice with ischemia‐induced arrhythmias had an accelerated early phase 1 repolarization of action potentials (APs) and a deeper "spike and dome" compared to control cardiomyocytes from non‐ischemia mice. Application of the antibody targeting at ANO1 pore prevented the ischemia‐induced early phase 1 repolarization acceleration and caused a much shallower "spike and dome". We conclude that ANO1 encodes CaCC and plays a significant role in the phase 1 repolarization of APs in mVMs. The ischemia‐induced increase in ANO1 expression may be responsible for the increased density of ICl.Ca in the ischemic heart and may contribute, at least in part, to ischemia‐induced arrhythmias. J. Cell. Physiol. 230: 337–346, 2015. © 2014 Wiley Periodicals, Inc.